PERANCANGAN CETAKAN UNTUK PRODUKSI PANEL BETON FLY ASH BOTTOM ASH - Ilham Maulana Prihutama; Sugiyanto Sugiyanto; Budi Setiyana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
An infrastructure project cannot be separated from using concrete for construction project. Concrete panels are one of the precast or precast concrete products, which are arranged in a clamp column for wall fence needs. This design aims to produce fly ash bottom ash concrete panels. Customer desires include affordable prices, high durability, compact dimensions, easy maintenance, available materials on the market, practical concrete panel installation, safety to use, light loads, easy manufacture, and qualify Indonesian National Standards. Then from some of the customer's wishes, several alternative product concepts were made with several alternative parts. From 72 alternative concepts total, the selected product concept was obtained at the 8th alternative product concept consisting of several parts. The selected parts are the main frame, side wall retainers, connections with nuts and bolts, work base, partition grooves with U grooving contours, connections with nuts and bolts, partition, partition locks, top partition retainers using square pipes with spaced plates, partition lock platform, outer sidewall and outer lock with vertical slot key. The process of producing fly ash bottom ash concrete panels have three SOP, there are the procedure for installing the concrete panel mold, the procedure for filling the concrete panel mold, and the procedure for removing the concrete panel mold.